Preparation and In vitro Evaluation of Isoniazid-Containing Dex-HEMA-Co-PNIPAAm Nanogels - Jafari, Maryam; Kaffashi, Babak (Ciência e Natura, 2015)
In this work, Dex-HEMA-Co-PNIPAAm nanogels containing Isoniazid antibiotic were made. Characteristic features of nanogels were studied by Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS) and scanning electron microscopy (SEM). Drug loading capacity and entrapment efficiency were determined. In vitro drug release amount was estimated at room and body temperature. Biocompatibility of gels was investigated through cytotoxicity assay. Finally antimicrobial properties of synthesized gels were studied. It was shown from the experimental data that the nanogels size after drug loading increased about 1-2%. %Isoniazid loading and %entrapment efficiency were in the range of 15-22% and 37-48% respectively. After 10 days of degradation ca. 80% at 25ºC and ca. 90% at 37ºC of the nanogel structures were destructed. No significant toxic product produced while degradation and all nanogels depicted good biocompatibility. No antimicrobial features observed through the test condition against gram negative E Coli.